Looking inside non-coding chloroplast regions of calophyllum brasiliense (calophyllaceae) to understand its southernmost population distribution - Percuoco, Cecilia Beatriz (2015)
In recent years the growing interest in the conservation of Paraná River’s riparian forest led to the discovery of botanical novelties for Argentina. Populations of Calophyllum brasiliense Camb. (Calophyllaceae), a typically flooded lowlands species, were identified in the remaining hygrophile forest of northeast Argentina and southeast Paraguay. Deforestation and flooding, due to the construction of dams, have caused these populations to suffer intensive fragmentation. The aim of this work was to infer phylogeographic relationships among five populations of C. brasiliense, three from Argentina and two from Paraguay, which represent the southernmost points of species’ distribution. We also compared them with samples of a C. brasiliense population from Mexico, the northernmost edge of the species distribution. The chloroplast intergenic spacers petG-trnP, psbJ-petA and the trnL-UAA chloroplast intron were amplified from leaves’ DNA. A total of 2234 bp were characterized once the three regions were analyzed. The three chloroplast regions showed nucleotide differences, represented by InDels, inversions and a few SNPs; however, only the trnL intron was selected for further phylogeographic analysis due to the amount of the information obtained for all populations. Based on trnL intron, it was possible to estimate nucleotide and haplotype diversity (π = 0.00237 and Hd = 0.29600, respectively). Three haplotypes were identified, which allowed Argentinean, Paraguayan and Mexican populations to be differentiated. Based on the three haplotypes found, we discuss and propose a model for a C. brasiliense’ geographic dispersion and historical colonization routes, including an alternative new one to the well-known of the Paraná River.